Regulation of MHC Class II-Peptide Complex Expression by Ubiquitination - Cho, Kyung Jin; Roche, Paul A. (Frontiers in Immunology, 2013)
MHC class II (MHC-II) molecules are present on antigen presenting cells (APCs) and these molecules function by binding antigenic peptides and presenting these peptides to antigen-specific CD4+ T cells. APCs continuously generate and degrade MHC-II molecules, and ubiquitination of MHC-II has recently been shown to be a key regulator of MHC-II expression in dendritic cells (DCs). In this mini-review we will examine the mechanism by which the E3 ubiquitin ligase March-I regulates MHC-II expression on APCs and will discuss the functional consequences of altering MHC-II ubiquitination.